2020
DOI: 10.3390/cells9051199
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Modulates Gap Junction Functionality and Connexin 43 and 26 Expression During TGF-β1–Induced Fibroblast to Myofibroblast Transition: Clues for Counteracting Fibrosis

Abstract: Skeletal muscle repair/regeneration may benefit by Platelet-Rich Plasma (PRP) treatment owing to PRP pro-myogenic and anti-fibrotic effects. However, PRP anti-fibrotic action remains controversial. Here, we extended our previous researches on the inhibitory effects of PRP on in vitro transforming growth factor (TGF)-β1-induced differentiation of fibroblasts into myofibroblasts, the effector cells of fibrosis, focusing on gap junction (GJ) intercellular communication. The myofibroblastic phenotype was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 111 publications
2
25
0
Order By: Relevance
“…Electrophysiological experiments were performed on C2C12 myotubes plated on glass coverslips and constantly superfused at a rate of 1.8 mL min −1 with a physiological external solution (mM): 150 NaCl, 5 KCl, 2.5 CaCl 2 , 1 MgCl 2 , 10 D-glucose and 10 HEPES (pH 7.4 with NaOH). The set-up, Axopatch 200 B amplifier, A/D-D/A interfaces Digidata 1200; Pclamp 6 software (Axon Instruments, Foster City, CA, USA) and electronic device were as described in detail in previously published papers [ 65 , 72 ]. The data analysis was made by Clampfit 9 (Axon Instruments, Foster City, CA, USA) software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological experiments were performed on C2C12 myotubes plated on glass coverslips and constantly superfused at a rate of 1.8 mL min −1 with a physiological external solution (mM): 150 NaCl, 5 KCl, 2.5 CaCl 2 , 1 MgCl 2 , 10 D-glucose and 10 HEPES (pH 7.4 with NaOH). The set-up, Axopatch 200 B amplifier, A/D-D/A interfaces Digidata 1200; Pclamp 6 software (Axon Instruments, Foster City, CA, USA) and electronic device were as described in detail in previously published papers [ 65 , 72 ]. The data analysis was made by Clampfit 9 (Axon Instruments, Foster City, CA, USA) software.…”
Section: Methodsmentioning
confidence: 99%
“…The cell linear capacitance C m , used as an index of the cell surface area (being the membrane-specific capacitance 1 μF/cm 2 ), is calculated from the area beneath the capacitive transient current and is the overall result of C s + C T . The membrane resistance (R m ) values were calculated from the steady-state membrane current (I m ) as previously reported [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cellular response observed in this work suggests that PRP nebulization does not affect the proliferation of lung fibroblasts, which would be involved in the repair processes. Cell migration and proliferation, and tissue repair [57,62] VEGF-A/TGF-β1 Fibroblast Antifibrotic effect [58,66] The present work shows that PRP nebulization does not entail a detriment of its composition or its bioactivity on cell cultures, in terms of cellular proliferation. However, it can cause a minor water evaporation throughout the nebulization process, and this could explain the slightly higher growth factors and cytokine levels in the nebulized PL in comparison with the standard one.…”
Section: Therapeutic Potential Of Platelet-rich Plasma Against Covid-19mentioning
confidence: 62%
“…Therefore, it is reasonable to assume that, as occurs in other tissues, the direct arrival of the nebulized platelet lysate molecules by the airway on lung cells will unleash a series of processes that affect the entire tissue, generating a biological environment favorable for healing. Relieving these processes of inflammatory reaction and tissue destruction also could lead to a modulated and less aggressive repair process, which, in addition to anti-fibrotic factors [ 58 , 66 ], could decrease or prevent pulmonary fibrosis. This prevention of fibrosis was already observed clinically in other tissues due to the reduction of inflammation and the repaired processes promoted by the PRP [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cappellari et al, taking Duchenne muscular dystrophy as a paradigm of defect in muscle regeneration, reviewed the main effects of drugs on regeneration biomarkers to assess whether targeting pathogenic events can help to protect niche homeostasis and enhance regeneration efficiency other than protecting newly formed fibers from further damage [15]. Squecco et al, reported the beneficial role of Platelet-Rich Plasma (PRP) treatment owing to PRP pro-myogenic and anti-fibrotic effects [16]. The main relevance of this study was the contribution toward defining the molecular and functional mechanisms regulating TGF-β1-induced fibroblast-myofibroblast transition, highlighting the role of Gap Junctions in this process as well as the involvement of voltage-dependent connexin isoform, namely Cx43.…”
mentioning
confidence: 99%